A Descriptive Cross-Sectional Study of Urinary Tract Abnormalities Utilizing Multi-Detector Computed Tomography Urography - Subhash Chandra Yadav; Sanju Rawal; Sadhan Mukhi; Darshana Dhakal (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Multidetector Computed Tomography Urography (MDCTU) is presently considered the preferred imaging modality for the urinary tract. Advanced MDCTU enables a comprehensive assessment of the kidneys, ureters, urinary bladder. MDCTU is commonly employed to investigate various conditions such as renal calculi, renal cysts, congenital kidney and ureter abnormali- ties, and speciﬁc renal inﬂammatory conditions. The objective of this study was to evaluate the diagnosis of various urinary tract abnormalities using MDCTU. MATERIAL AND METHODS This descriptive cross-sectional study was conducted from June to August 2023, at the Department of Radiodiagnosis & Medical Imaging, Universal College of Medical Sciences and Teaching Hospital, Bhairahawa, Nepal, examined a total of ﬁfty-nine patients. The examination protocol comprised triphasic techniques, which included unenhanced, nephrographic, and excretory phases, utilizing a MDCT scanner. The descriptive data were analyzed using SPSS version 20 and presented in the form of a number and percentage. RESULTS A total 59 patients, 32 were male and 27 were female. Mean age of patients were 44.17±15.66 years, with the majority (28.81%) falling within the age range of 20-30 years. Abdominal pain was the most common symptom (79.66%), followed by hematuria (18.64%). Urolithiasis was the most frequent diagnosis (47.46%), followed by ureterohydronephrosis (22.03%) and hydrone- phrosis (18.64%). Inﬂammatory change/infection affected 13.56% of patients, while congenital abnormalities were the least prevalent (3.39%). CONCLUSION MDCT urography is considered the optimal modality for detecting a broad range of urinary tract abnormalities, due to its utilization of a combination of unenhanced, nephrographic-phase, and excretory-phase imaging techniques.